A dictionary of literary devices : gradus, A-Z - Dupriez, Bernard Marie, 1933- (University of Toronto Press, 1991)
Comprising some 4000 terms, defined and illustrated, ""Gradus"" calls upon the resources of linguistics, poetics, semiotics, socio-criticism, rhetoric, pragmatics, combining them in ways which enable readers quickly to comprehend the codes and conventions which together make up 'literarity.'